Bylaw and strategy for the Ethiopian Landscape Restoration Platform(ELaRP) - Adimassu, Zenebe; Belay, Berhanu; Dadi, Mulugeta Belete; Adgo, Eneyew; Toru, Tessema; Hailu, Mengesteab; Tibebe, Degefie; Abera, Wuletawu; Tamene, Lulseged (2024)
Establishing the Ethiopian Landscape Restoration Platform (ELaRP) is crucial as it serves as a hub for various stakeholders, facilitates the exchange of best practices and research findings, influence policies that promote landscape restoration and attract funding for restoration initiatives. Overall, ELaRP is essential for fostering a holistic, sustainable approach to land restoration in Ethiopia, addressing both environmental and socio-economic challenges. To ensure the proper functioning of the ELaRP, bylaw and strategy document were developed by the steering committee and approved by the general assembly. The bylaw of ELaRP outlines the governing rules and regulations for the platform. It includes provisions for membership criteria, decision-making processes, financial management, and accountability mechanisms. It helps to ensure transparency, accountability, and consistency in how the platform functions. Specifically, bylaws define membership criteria, outline roles and responsibilities, establish financial protocols, and provide a mechanism for conflict resolution. Clear and well-defined bylaws is essential for maintaining organizational integrity, fostering trust among members, and achieving the platform's goals effectively. A five-year and annual strategic plan was developed to monitor the proper functioning of ELaRP. The strategy includes activities, indicators and a timeline for implementation. Having a well-defined strategy for a landscape restoration platform is essential for setting clear goals, outlining action plans, and guiding decision-making processes. A strategic approach helps in identifying priority areas of intervention, allocating resources efficiently, and measuring progress towards desired outcomes. For example, the strategy for the ELaRP involves research, stakeholder engagement, capacity building, monitoring, evaluation and knowledge sharing initiatives to ensure the success of restoration efforts in Ethiopia. By having a strategy in place, landscape restoration platforms can enhance their impact, attract funding and partnerships, and contribute effectively to sustainable land management. and biodiversity conservation.